CONSTRUCTION OF A MODEL TO EVALUATE THE INFORMATION SEEKING BEHAVIOUR OF THE UNIVERSITY ACADEMICS - Sivasanthiran, A.; Samaradiwakara, Manoja Nilanthi (My University, 2020)
A significant portion of the clientele of the university libraries is made up of the academic (teaching) staff. Therefore, these libraries are responsible for systematically understanding the information requirements and usage patterns of those academics, in order to better serve them. Hence, a theoretical model developed exclusively for these academics becomes crucial. Therefore, this study evaluated various models on the information seeking behaviour of diverse user groups with the aim of constructing a model to study the information seeking behaviour of the academics. This qualitative analysis involved reviews of both theoretical literature of six influential information seeking models, and empirical literature within various disciplines. Out of an in-depth evaluation, the Leckie model (1996) for professionals was adopted, where work roles and tasks, information needs, resources used and level of awareness of information were identified to be the key factors influencing the information seeking behaviour of academics. Further, two additional factors identified via empirical researches were appropriately placed into this model: those are personal factors and information searching strategies. This study also redefined these factors by incorporating suitable variables, and proposed that Factor Analysis is used to understand the contribution of each factor towards the information seeking behaviour of academics. It also keeps provisions for future researchers to customize the above factors to suit different disciplines/field of study or countries. Hence, this model can be used by the university librarians or other researchers to methodologically study the information needs and the seeking patterns of the faculties.
Keywords: Information seeking behaviour, Information needs, Information resources, Leckie model, University academics